The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.3389/fnins.2021.651192
|View full text |Cite
|
Sign up to set email alerts
|

Decreasing the Surgical Errors by Neurostimulation of Primary Motor Cortex and the Associated Brain Activation via Neuroimaging

Abstract: Acquisition of fine motor skills is a time-consuming process as it is based on learning via frequent repetitions. Transcranial electrical stimulation (tES) is a promising means of enhancing simple motor skill development via neuromodulatory mechanisms. Here, we report that non-invasive neurostimulation facilitates the learning of complex fine bimanual motor skills associated with a surgical task. During the training of 12 medical students on the Fundamentals of Laparoscopic Surgery (FLS) pattern cutting task o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
2

Relationship

4
5

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 46 publications
2
16
0
Order By: Relevance
“…Then, in a bimanual pattern cutting study with tDCS of the M1 along with portable neuroimaging [3], Gao et al observed that the M1 tDCS effect on the performance error was significant (p < 0.001; t-test when normally distributed or Mann-Whitney U test when not) after day 7 when compared to the sham group. Here, a delayed effect of M1 tDCS after day 7 was found that is postulated to be related to the emergence of M1 activation that was significant (p < 0.001) only during the latter learning stage (day 7-12) when compared to the initial learning stage (day 2-6) [3]. This is expected from known in vivo effects of tDCS that do not change the firing rates of the cortical neurons [31] but modulate endogenous task-specific brain activity [32], so neuroimaging can provide the "target" cortical activation related to endogenous task-specific brain activity.…”
mentioning
confidence: 71%
See 1 more Smart Citation
“…Then, in a bimanual pattern cutting study with tDCS of the M1 along with portable neuroimaging [3], Gao et al observed that the M1 tDCS effect on the performance error was significant (p < 0.001; t-test when normally distributed or Mann-Whitney U test when not) after day 7 when compared to the sham group. Here, a delayed effect of M1 tDCS after day 7 was found that is postulated to be related to the emergence of M1 activation that was significant (p < 0.001) only during the latter learning stage (day 7-12) when compared to the initial learning stage (day 2-6) [3]. This is expected from known in vivo effects of tDCS that do not change the firing rates of the cortical neurons [31] but modulate endogenous task-specific brain activity [32], so neuroimaging can provide the "target" cortical activation related to endogenous task-specific brain activity.…”
mentioning
confidence: 71%
“…Surgical skill acquisition may be facilitated with a safe application of transcranial electrical stimulation (tES) [1]. Transcranial direct current stimulation (tDCS), a tES modality, has been shown to facilitate surgical skill learning when applied to cortical targets, including the primary motor cortex [2,3], the supplementary motor area [2], and the prefrontal cortex [4]. Prior work has shown that tDCS facilitated complex motor tasks performed during surgical skill training, including laparoscopic technical skills training [5] and tumor resection in neurosurgery [6].…”
mentioning
confidence: 99%
“… 1 4 HbO and HbR time series can reflect changes in neurovascular coupling and hence, neuronal activity. fNIRS has been widely used in cognitive, 5 9 motor skill studies, 10 15 and brain–computer interface technique. 16 …”
Section: Introductionmentioning
confidence: 99%
“…Then, the hierarchy of cognitive control during skill learning shows a rostrocaudal axis in the frontal lobe 45 , where a shift from posterior to anterior is postulated to mediate the progressively abstract, higher-order control expected from experts. Numerous functional magnetic resonance imaging (fMRI) and fNIRS studies have been published on skill learning 33,46,47,48,49,50,51,52,53 , including training under stress 54 ; however, these studies have not systematically investigated the directional cortical information ow 55,56 , its variability during FLS skill acquisition in physical versus VR simulators, and its interaction with the skill level based on statistical path analysis 57,58 . fNIRS-based brain imaging has limited spatial and depth sensitivity 59 .…”
Section: Introductionmentioning
confidence: 99%